Effect of Substitution of Cowpea Sprouts Flour (Vigna unguiculata L.) and Sorghum Flour (Sorghum bicolor L.) of Chemical Quality and Organoleptic Quality on Biscuits as Supplementary Feeding Recovery for Protein Energy Malnutrition School Age Children - Puspa D., Amalia Resa; Razak, Maryam; Pudjirahaju, Astutik (Journal of Local Therapy, 2024)
Abstract: Malnutrition status in school-age children (5 – 12 years) based on BMI/U nationally reaches 9.2% (very thin category 2.4% and thin 6.8%) while the prevalence of malnutrition in East Java Province is 8% and Malang city region is 7.69%. Overcoming PEM in school-age children by providing diet therapy in the form of Providing Supplementary Food to School Children (PMT-AS). Additional food based on local food ingredients using cowpea sprout flour (Vigna unguiculata L.) and sorghum flour (Sorghum bicolor L.). The aim of the research was to analyze the effect of substitution of cowpea sprout flour and sorghum flour on the chemical quality and organoleptic quality of biscuits as PMT for PEM school-age children. This type of experimental research with a RAL design consists of 4 treatment levels with 3 repetitions, namely P0 (100:0:0), P1 (40:55:5), P2 (40:45:15), P3 (40:35:25). The chemical quality results of biscuits using the calculated value method are carbohydrate content (59.27 – 62.27 g/100 g), protein content (7.31 – 10.56 g/100 g), fat content (16.16 – 16.64 g/100 g), and energy value (423.75 – 428.45 Kcal). The organoleptic quality of biscuits had a significant effect on the panelists’ liking for color (p=0.000), taste (p=0.000), and aroma (p=0.000) but did not have a significant effect on texture (p=0.221). The best formulation of PMT biscuits with the substitution of cowpea sprout flour and sorghum flour for PEM school-aged children is treatment P2 (40:45:15).